Social Movements and Collective Action - Staggenborg, Suzanne (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The course begins with a rich survey of social movement history that climaxes mid-semester with the cultural critique of social movement theory. This unresolved tension is carried through the rest of the course, as it explores some thematic areas including leadership, guerilla movements, the Women’s Movement, "normal" politics, global movements, and others.